Chemical and physical characteristics of meat from Cinta Senese, Large White and related cross pigs reared indoors - Franci O.; Pugliese C.; Acciaioli A.; Campodoni G.; Bozzi R.; Gandini G. (Tradition and innovation in Mediterranean pig production, 2000)
Twenty-nine Cinta Senese (CS), 12 Large White (LW) and 29 Large White x Cinta Senese (LWxCS) pigs were reared under intensive conditions and slaughtered at an average weight of 140 kg and an average age of 312 d (CS), 273 d (LWxCS) and 259 d (LW). The colour of the fat was measured on the side. pH, colour, chemical composition, water loss and shear force were determined on the Longissimus lumborum muscle. The CS animals had fat with lower values of L*, b* and hue, and higher values of a* and chroma. Pork from CS was more acceptable in colour (lower hue values) and was like LWxCS in being more highly coloured because of the contribution of red. pHu was higher in CS than in the other two genotypes (5.78 compared with 5.66 and 5.51). Fat content was higher in CS (3.19 per cent on wet basis) than in LWxCS (2.25 per cent) or LW (0.88 per cent) but moisture was lower in CS than in the other genotypes. Water holding capacity was higher in CS than in LW. Meat from CS had a greater shear force when raw, but tenderness similar to that of the other genotypes after cooking.
4. International Symposium on Mediterranean Pig, 1998/11/26-28, Evora (Portugal)